I am giving up on these funcitons. If anyone can post a step-by-step visual aid on how to get the derivatives for these two suckers that would be great.
1) sqrt(x)-cubrt(x)
2)3x/(x^2+4)
Hi AFireInside,
Don't give up just yet. I can help.
$\displaystyle \displaystyle \sqrt{x}-\sqrt[3]{x} = x^{\frac{1}{2}}- x^{\frac{1}{3}}$
Now apply the power rule $\displaystyle \displaystyle f(x)= x^n \implies f'(x) = nx^{n-1}$
With this one try
$\displaystyle \displaystyle y = \frac{f(x)}{g(x)}\implies y' = \frac{g(x)\times f'(x)-f(x)\times g'(x)}{g(x)^2}$